2017
DOI: 10.1186/s12954-017-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring quality and coverage of harm reduction services for people who use drugs: a consensus study

Abstract: Background and aimsDespite advances in our knowledge of effective services for people who use drugs over the last decades globally, coverage remains poor in most countries, while quality is often unknown. This paper aims to discuss the historical development of successful epidemiological indicators and to present a framework for extending them with additional indicators of coverage and quality of harm reduction services, for monitoring and evaluation at international, national or subnational levels. The ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 125 publications
0
35
0
3
Order By: Relevance
“…The longitudinal analysis of annual treatment participation has a close relationship with the recently proposed cross-sectional "coverage" indicator for OAT, that is, the number of patients in OAT divided by the estimated prevalence of high-risk opioid use [28]. As the coverage denominator also includes high-risk opioid users who have never entered OAT, the adjusted treatment participation multiplied with the proportion of high-risk opioid users having ever been in OAT will correspond with coverage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The longitudinal analysis of annual treatment participation has a close relationship with the recently proposed cross-sectional "coverage" indicator for OAT, that is, the number of patients in OAT divided by the estimated prevalence of high-risk opioid use [28]. As the coverage denominator also includes high-risk opioid users who have never entered OAT, the adjusted treatment participation multiplied with the proportion of high-risk opioid users having ever been in OAT will correspond with coverage.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, if an adjusted treatment participation of 50% and a 45% OAT coverage are known for a specific region and year, the proportion of high-risk opioid users who have never been in OAT can be estimated. Thus, the combination of adjusted treatment participation and coverage estimates may lead to profound insights as to how the OAT coverage could be improved in a "harm reduction cascade model" as successfully established for other chronic health conditions [28].…”
Section: Discussionmentioning
confidence: 99%
“…A second study made comparable projections for other European countries, but also found that some countries would need to scale‐up opioid substitution therapy (OST) and needle and syringe exchange programmes (NSP) interventions to reduce chronic HCV prevalence . Yet in most countries of the world, particularly low‐ and middle‐income countries, access to DAAs and harm reduction services remains extremely limited , and achieving the WHO targets will require major expansion of both forms of access . That is because besides DAA therapy, which enables a sustained virologic response (SVR), the most effective form of HCV prevention for PWID is harm reduction, including OST, NSPs, and supervised injecting centres.…”
Section: Introductionmentioning
confidence: 99%
“…As experiências internacionais têm demonstrado que onde as políticas de redução de danos estão em vigor, as economias dos custos em saúdecomo, por exemplo, na redução das infecções virais de pessoas com HIV e hepatite Ce a melhoria da qualidade de vida das pessoas que usam drogas, estão sendo percebidas e comprovadas pelas práticas de intervenção, tal como prover drogas de forma sistemática e monitorada para usuários dependentes. Intervenções mais amplas, abarcando legislações e políticas públicas de provisão, como algumas verificadas em países da Europa, estão possibilitando a redução dos crimes e prisões vinculadas ao uso de drogas e a redução da mortalidade por overdose (Wiessing et al, 2017).…”
Section: Introductionunclassified
“…Todavia, na maioria dos países, as ações de redução de danos continuam centradas nos indivíduos e não em políticas mais amplas que incluem aspectos estruturais e mudanças nas legislações (Menéndez, 2012). Sem enfrentamento desta situação também se torna difícil monitorar a eficácia dos serviços de redução de danos, pois estes produzem melhores resultados quando combinadas as várias estratégias de intervenções (Wiessing et al, 2017).…”
Section: Introductionunclassified